Endovascular bypass for salvage of vascular access in hemodialysis catheter-consigned patients. Issue 6 (November 2018) - Chen, Matt Chiung-Yu; Weng, Mei-Jui; Liang, Huei-Lung
Purpose: This study was performed to retrospectively assess the efficacy of percutaneous creation of an intervascular bypass with or without stent graft deployment (endovascular bypass) for salvage of abandoned vascular access sites in hemodialysis catheter-consigned patients. Methods: Salvage of abandoned vascular access sites was attempted in 16 patients with hemodialysis catheters. These vascular access sites were salvaged using endovascular bypass techniques to redirect the access flow to a nonarterialized vein as a new outflow conduit or cannulation segment. The postintervention primary, assisted primary, and secondary patency rates of the access site and bypass were calculated using the Kaplan–Meier method. Results: The procedural and clinical success rates were both 100%. The postintervention primary patency rate of the bypass and access site at 360 days was 75.7 ± 12.5% and 56.8 ± 14.9%, respectively. The mean follow-up period was 461.9 days (range: 121–900 days). No major complications were observed. One bare bypass tunnel rupture and one pseudoaneurysm were noted during the procedure. Conclusion: Salvage of abandoned vascular access sites for hemodialysis catheter-consigned patients can be technically feasible and clinically successful using endovascular bypass techniques in selected patients when surgical revision is not considered or is not possible.